Amplitude Dependence of Nonlinear Precipitation Blocking of Relativistic Electrons by Large Amplitude EMIC Waves - Jacob Bortnik; Jay M. Albert; Anton Artemyev; Wen Li; Chae‐Woo Jun; Veronika S. Grach; Andrei G. Demekhov (Geophysical Research Letters)
Abstract Recent work has shown that ElectroMagnetic Ion Cyclotron (EMIC) waves tend to occur in four distinct regions, each having their own characteristics and morphology. Here, we use nonlinear test‐particle simulations to examine the range of energetic electron scattering responses to two EMIC wave groups that occur at low L‐shells and overlap the outer radiation belt electrons. The first group consists of low‐density, H‐band region b waves, and the second group consists of high‐density, He‐band region c waves. Results show that while low‐density EMIC waves cannot precipitate electrons below ∼16 MeV, the high density EMIC waves drive a range of linear and nonlinear behaviors including phase bunching and trapping. In particular, a nonlinear force bunching effect can rapidly advect electrons at low pitch‐angles near the minimum resonant energy to larger pitch angles, effectively blocking precipitation and loss. This effect contradicts conventional expectations and may have profound implication for observational campaigns.